Risk Factors for Congenital Malformations among Population in the Agadir Region at Morocco - SAID EL MADIDI; Bouadil Karim (Alta Dharma Publisher, 2021)
A prospective case-control study at the regional level was conducted in the pediatrics and neonatology department of Hassan II hospital in Agadir in Morocco from April 2016 to April 2018. In this study, we aimed to study congenital anomalies in the population of the study region regarding the frequency and highlight the associated risk factors. The types of congenital malformations have been classified according to the International Classification of Diseases (ICD-10). Univariate analyzes were performed to identify the variables associated with the etiology of the malformations. Multiple logistic regression was used to characterize the associations between the MC, and the determining explanatory variables are taken into account simultaneously. The results found that congenital disabilities were significantly associated with the consanguinity level of the child, the prematurity of childbirth, the family history of CMs, the Body Mass index. (BMI) of the mother and the presence of a significant trauma during pregnancy. Our results have made it possible to highlight the existence of an association between a certain number of risk factors and the occurrence of congenital malformations